A funtion for the Argentine export demand - Streb, María Luisa (2005)
Considering the fact that exports can be a driving force of growth, the purpose of the paper is to make an estimation of the Argentine export demand. As the exports are defined as a function of the income of the main trade partners and the relative prices, the income and price elasticities were obtained. Making use of the time-series techniques to detect for non stationarity, an ARDL model was estimated with OLS and 2SLS methods. The main findings are that exports are very sensitive to income but not to prices, suggesting that an impact of a real devaluation would not necessary improve the performance of the exports.